1967
DOI: 10.2136/sssaj1967.03615995003100030009x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Water Content‐Pressure Head Data Obtained by Equilibrium, Steady‐State, and Unsteady‐State Methods

Abstract: The water content-pressure head relationship for a small, well-confined, rectangular sample of fine sand was obtained under different water flow conditions. Water contents were measured by a gamma system and pressure heads were measured by a tensiometer-pressure transducer combination. During drying, more water was retained in the sand at a given pressure head in the unsteady flow case than in the static equilibrium and steadystate cases, which agreed with each other.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
105
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(128 citation statements)
references
References 0 publications
21
105
0
2
Order By: Relevance
“…8 that the dynamic capillary pressure curves are always above the steady state capillary pressure curve. This is consistent with experimental observations of Topp et al (1967), who compared the correlation between capillary force and water saturation during steady and unsteady flows, observed that during unsteady state, the dynamic capillary pressure is significantly higher than that performed under equilibrium or steady state. Topp et al (1967) Fig.…”
Section: Unsteady State Capillary Pressure Curvesupporting
confidence: 92%
See 1 more Smart Citation
“…8 that the dynamic capillary pressure curves are always above the steady state capillary pressure curve. This is consistent with experimental observations of Topp et al (1967), who compared the correlation between capillary force and water saturation during steady and unsteady flows, observed that during unsteady state, the dynamic capillary pressure is significantly higher than that performed under equilibrium or steady state. Topp et al (1967) Fig.…”
Section: Unsteady State Capillary Pressure Curvesupporting
confidence: 92%
“…Hence, the capillary pressure-saturation relationship curves obtained under equilibrium conditions cannot adequately describe the relationship between capillary force and saturation within hours. In fact, Topp et al (1967), Davidson et al (1966), Smiles et al (1971), and Vachaud et al (1972) showed that both the retention characteristic and the hydraulic conductivity characteristic are different under the static equilibrium/steady state and unsteady state cases, and they depend on both the history and the change in rate of saturation. Hence, if dynamic non-equilibrium occurs between the water content and the water potential during transient water flow, the water retention characteristic measured in the laboratory under equilibrium cannot be reliably applied to that under transient flow.…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies address drainage and imbibition behavior on a laboratory scale, which describe only one facet of multiphase flow in fractured reservoirs. Experimental evidence [14,34,35,51,52,54,56,58,59,63] supports a more general description of capillary pressure and relative permeability functions, which includes a nonequilibrium effect. Reservoir interpretation that does not recognize the potential for reduced recovery because of non-equilibrium effects may lead to an overestimation of the recovery.…”
Section: Introductionmentioning
confidence: 61%
“…For water-wet media with a finite contact angle, it is possible that the delay time is a few months. This effect is observed in many spontaneous imbibition experiments [14,34,35,51,52,54,56,58,59,63]. During the transition, the wetting-fluid relative permeability is higher than in steady-state conditions.…”
Section: Non-equilibrium Effectsmentioning
confidence: 75%
“…Accordingly, the capillary pressure data obtained in an experiment may not be correct unless the P c -S w relationships account for their dependence on the rate of change of fluid saturation (dS w /dt). A number of experiments have shown that the P c -S w curves at equilibrium and dynamic conditions are different (Topp et al 1967;Smiles et al 1971;Vachaud et al 1972;Mirzaei 2012, 2013;Mirzaei and Das 2013). The dependence of the capillary pressure curves on dS w /dt is known as the dynamic effect in capillary pressure relationship Mirzaei and Das 2007;Das et al 2007).…”
Section: Introductionmentioning
confidence: 99%